Combination of palonosetron-dexamethasone is more effective than ondansetron-dexamethasone as single cisplatin antiemetic chemotherapy - Putra, Agung Sunarko; Suhatno, Suhatno (Majalah Obstetri & Ginekologi, 2018)
Objective: To know the efficacy differences between two groups of drug combination ondansetron-dexamethasone (A) and ondan-setron-dexamethasone (B) to prevent emetic rsponses after chemotherapy cisplatin administration (CINV). Materials and Methods: A prospective double blind randomized clinical trial study held in Dr. Soetomo General Hospital involving 66 subjects, devide into two groups randomly 33 patients each. One group receive palonosetron-dexamethasone combination therapy compare to ondansetron-dexamethasone combination as standart therapy in gynecologic oncology Dr. Soetomo Hospital in a control group as cisplatin chemotharapy CINV prophylaxis. The research was conducted from June till October 2014 in the Dr. Soetomo General Hospital-Surabaya. Assessment and measurement of the response of nausea and frequency of vomiting according Gralla scale, changes in plasma density and electrolyte serum (Na, K, and Cl) as a result of dehydration caused by nausea and vomiting, as well as counting the onset of nausea and vomiting occur. Results: There was significant differences between the results of the combination therapy compared ondansetron-dexamethasone to palonosetron-dexamethasone for nausea and vomiting (p=0,001). 31 subjects suffers nausea in ondansetron group, while 9 subjects suffers nausea in palonosetron group. Vomiting occurs in 17 subjects from ondansetron group, and only 1 subject from palono-setron group during study. Changes in plasma density significant in palonosetron group, and natrium in ondansetron group. For K and Cl not significantly difference in both groups before and after cisplatin chemotherapy administration. Conclusion: Palonosetron-dexamethasone combination is super-ior as cisplatin CINV prophylaxis in response to nausea and vomiting frequency, and also give longer protection compare to ondansetron-dexamethasone significantly. The plasma density and electrolyte serum changes are varied in numbers and also influenced by many factors including physical status and nutrition, also intake of each patients.